The Role of Aberrant Metabolism in Cancer: Insights Into the Interplay Between Cell Metabolic Reprogramming, Metabolic Syndrome, and Cancer - Yu, Yina; Gong, Liang; Ye, Jun (Frontiers in Oncology, 2020)
Metabolic syndrome (MetS) is characterized by hyperglycemia, hypertension, dyslipidemia and abdominal obesity. Patients with MetS or other metabolic disorders are more susceptible to cancer development and recurrence and have a worse long-term prognosis. Moreover, the metabolic reprogramming observed in cancer cells has also been described as one of the new hallmarks of cancer. Thus, aberrant metabolism has been proposed as an important risk factor for cancer. Chronic inflammation, reactive oxygen species (ROS), and oncogenic signaling pathways are considered as main potential triggers. Considering the strong association between metabolism and cancer, metabolism-modulating drugs, including metformin and statins, as well as adopting a healthy lifestyle, have been extensively investigated as strategies to combat cancer. Furthermore, strategies that interfere with the metabolic rewiring of cells may also have potent anti-cancer effects. In this article, we provide a comprehensive review of current knowledge on the relationship between aberrant metabolism and cancer and discuss the potential use of metabolism-targeting strategy for the treatment of cancer.